THE ROLE OF COMPENSATION AND WORK ENVIRONMENT IN IMPROVING PERMANENT TEACHER PERFORMANCE IN RELIGION DEPARTMENT OF DEMAK - Yeni Rahman (UNISSULA, 2017)
Compensation is an important factor for improving the performance of employees. Work environment, either physical or non-physical is also an important variable affecting directly or indirectly against theperformance of employee performance. This research is done by using SEM (Structural Equation Modeling) test, and SmartPLS application. The research was done by giving questionnaire to 62 permanent teachers in a foundation under religion department, Demak Central Java. In term of considering the number of sample, the writer uses solvin formula with proportional random sampling technique. Multiple regression analysis method is used to analyze compensation impact and work environment towards teachers’ performance. The result of this research shows that there is a significant impact from compensation and the work environment towards teachers’performance with R-square 0,642. It shows that the improvement of compensation and works condition will improve teachers’ performance.Key Words: Compensation, Works Environment, Performance, SPSS.